Biología reproductiva de Prochilodus nigricans, (Agassiz, 1829) “boquichico” Y Arapaima gigas (Cuvier, 1829) “paiche” en el Bajo Amazonas, San Pablo, Loreto - Perú, 2021 - Padilla Pérez, Daniela (2022)
The objective of this work was to determine the size at first sexual maturity, determine the sexual proportion and evaluate the gonadosomatic index of the fish Prochilodus nigricans and Arapaima gigas. During the months of November 2020 to October 2021, individuals of P. nigricans and A. gigas were collected from markets, ports and fishing areas of the lower Amazon in the San Pablo district in the Loreto region. A total of 433 individuals of Prochilodus nigricans were recorded (females = 246 ind., 56.80% and males = 187, 43.20%) and 10 individuals of Arapaima gigas (females = 5 ind., 50%; males = 3 ind., 30 % and indeterminate = 2 ind., 20%). A sex ratio of 1.3:1 in favor of P. nigricans females and 1.6:1 in favor of A. gigas females was determined. The size at sexual maturity for P. nigricans was estimated at a total length of 24.8 (24.6 – 25.1 cm) in females and a total length of 24.2 (23.9 – 24.6 cm) in males. The gonadosomatic index presented high values in the months of November (IGS of 16.9% in females and 1.39% in males) and December (IGS of 13.5% in females and 1.24% in males). While for Arapaima gigas it was not possible to determine the size at first sexual maturity and gonadosomatic index, ecause there was not enough number of individuals during the sampling period.